Maps of a Nation? The Digitized Ordnance Survey for New Historical Research. (17th April 2021) - Hosseini, Kasra; McDonough, Katherine; van Strien, Daniel; Vane, Olivia; Wilson, Daniel C S
Abstract: Although the Ordnance Survey has itself been the subject of historical research, scholars have not systematically used its maps as primary sources of information. This is partly for disciplinary reasons and partly for the technical reason that high-quality maps have not until recently been available digitally, geo-referenced, and in color. A final, and crucial, addition has been the creation of item-level metadata which allows map collections to become corpora which can for the first time be interrogated en masse as source material. By applying new Computer Vision methods leveraging machine learning, we outline a research pipeline for working with thousands (rather than a handful) of maps at once, which enables new forms of historical inquiry based on spatial analysis. Our 'patchwork method' draws on the longstanding desire to adopt an overall or 'complete' view of a territory, and in so doing highlights certain parallels between the situation faced by today's users of digitized maps, and a similar inflexion point faced by their predecessors in the nineteenth century, as the project to map the nation approached a form of completion.